Economic crisis impact on international financial institutions: The necessity for reforms - Petrović Pero; Jović Željko (Međunarodni Problemi, 2013)
The emergence and deepening of the global economic crisis is reflected in large part on the functioning of international financial institutions and their current structure. The long-term financial crisis has placed demands for decisive reform moves in the functioning and structure of the IMF, the World Bank Group and other global and regional financial institutions. This means that so far, the results of their policies have been inadequate and that their role is subject to critical observation finding an efficient performance of financial markets. The crisis has imposed the need to reform international financial institutions and the new global financial architecture. Changes in structure and their functioning should lead to the global economic stability. Members of the Euro zone are faced with a new attitude towards the international financial institutions and the International Monetary Fund, in particular. The proclaimed missions of the International Monetary Fund and the World Bank are clearly separated in theory, but with the passing of time, their activities have become increasingly intertwined, so that they often include a name - international financial institutions.